Effect of Bifurcation Angle Configuration and Ratio of Daughter Diameters on Hemodynamics of Bifurcation Aneurysms - Farnoush, A.; Avolio, A.; Qian, Y. (American Journal of Neuroradiology, 2013)
BACKGROUND AND PURPOSE: EL associated with ruptured aneurysms is higher than that for unruptured aneurysms. In this study, the effect of arterial morphologic variation of bifurcation aneurysms on EL was investigated in idealized models of middle cerebral artery aneurysms. MATERIALS AND METHODS: Bifurcation angle configuration and DA ratio were evaluated in 6 idealized numeric models. Type A and B bifurcation models were defined with symmetric and asymmetric bifurcation angles of 136°, and 57° and 79°, respectively. Three models with DA ratios of 1, 1.3, and 2 were constructed for each type. EL was calculated as the energy difference between aneurysm inflow and outflow at the aneurysm neck. Three growth paths (R1, R2, and R3) were proposed. RESULTS: The highest EL and influx occurred in bifurcations with DA ratios of 1 for both types A and B. As the DA ratio increases, flow distribution between branches becomes more asymmetric, resulting in a reduction of EL and intra-aneurysmal flow. No strong relation was found between bifurcation angle configuration, inflow flux, and EL. EL decreased with an increase in the AR and DA ratio and increased with an increase in the AR and reduction of DA ratio. CONCLUSIONS: EL determined in idealized models is less dependent on bifurcation angle configuration than on DA ratio, and the stability of the aneurysm strongly depends on variation of the daughter artery morphology after aneurysm growth. ARaspect ratioDAdaughter artery diameterELenergy lossLSAlow shear stress areaR1increasing the AR and DA ratioR2increasing the AR and reducing the DA ratioR3increasing the AR with a constant DA ratioWSSwall shear stress